An unusual case of small bowel obstruction secondary to internal herniation of distal ileum through a rent between adhered inflamed vermiform appendix and appendices epiploicae - H. G. M., Rudraiah; Davis, Benita (International Surgery Journal, 2021)
Intestinal obstruction secondary to an internal hernia is rare and that occurring through a rent between the adhered inflamed vermiform appendix and appendices epiploicae of the proximal caecum is so rare that this case was the first of its kind ever to be reported. Such a cause for obstruction should be suspected in a patient with a virgin abdomen with no history/clinical features of an obstructing external hernia or abdominal tumor. A 28 year old man presented to the ER with features of intestinal obstruction, in whom CECT abdomen revealed multiple dilated small bowel loops with breaking-of seen in the region of the terminal ileum. Surgical exploration revealed internal herniation of the distal ileum through a rent between the adhered inflamed vermiform appendix and the appendices epiploicae of the proximal caecum; reduction of which was sufficient to relieve the obstruction and demonstrate healthy reperfusion. Adhesiolysis, epiploicae appendectomy and appendectomy was done with no other points of obstruction along the small bowel. Due to its rarity, non-specific presentation pattern and limited usefulness of imaging for diagnosis, a high index of suspicion with prompt early surgical exploration is a must for a successful outcome in such cases intestinal obstruction; especially in a virgin abdomen.